Real-world efficacy of low dose osimertinib as second-line treatment in patients with epidermal growth factor receptormutated advanced non-small cell lung cancer - Mau, Ern Poh; Balakrishnan, Sivasubramaniam; Tan, Sin Nee; Zainal Abidin, Muhammad 'Adil; Liam, Chong-Kin; Tan, Jiunn Liang; Pang, Yong Kek; Alaga, Arvindran; Tho, Lye Mun; How, Soon Hin (AME Publishing Company, 2024)
Background: Response rates of epidermal growth factor receptor (EGFR)-mutated advanced non-small cell lung cancer (NSCLC) to lower doses of osimertinib [20 mg once daily (OD) and 40 mg OD] are similar to those of the recommended dose of 80 mg OD, but there is a lack of real-world evidence on the effect of the lower doses of osimertinib on survival outcomes. We conducted this study to assess the efficacy and safety of lower osimertinib doses for patients with EGFR-mutated advanced NSCLC whose disease had progressed on earlier generation EGFR tyrosine kinase inhibitors (TKIs) in a real-world clinical practice. Methods: This multicenter, retrospective study included patients with EGFR-mutated advanced NSCLC treated with low doses of osimertinib after failing first- or second-generation EGFR TKIs due to acquired T790M mutation. Data on demographics, staging, treatment history, best overall response rate (ORR) based on RECIST 1.1, and adverse events (AEs) were collected from the patients’ case notes. Descriptive data were described in percentages and medians. Progression-free survival (PFS) and overall survival (OS) were calculated using the Kaplan-Meier method. Results: Of the 22 patients studied [males =8 and females =14; Eastern Cooperative Oncology Group (ECOG) 1 or 2 =7 and ECOG 3 or 4 =15], 45.5% were on 40 mg OD, 31.8% were on 80 mg every other day (EOD), and 22.7% on 40 mg EOD. First-line EGFR TKIs used included afatinib, erlotinib, and gefitinib. The ORR with lower doses of second-line osimertinib was 77.3%. Overall, the median PFS was 10.0 months [95% confidence interval (CI): 8.6–11.4] and median OS was 13.0 months (95% CI: 9.4–16.6). In patients with ECOG 1 or 2, the median PFS was 18.0 months (95% CI: 5.8–30.2) and the median OS was not reached at the time of analysis. In patients with poor ECOG performance status of 3 and 4, good survival outcomes were also seen with a median PFS of 7.0 months (95% CI: 4.7–9.3) and median OS of 10.0 months (95% CI: 7.5–12.5). All AEs except one case of paronychia were Grade 1. There were no Grade 3 or 4 AEs. Conclusions: Treatment with low dose osimertinib demonstrated good efficacy and tolerability in EGFRmutated advanced NSCLC patients who failed first-line treatment with first- or second-generation EGFR TKIs due to T790M mutation